Magnetically Controlled Liposome Aggregates for On-Demand Release of Reactive Payloads - Haša, Jan; Hanuš, Jaroslav; Štěpánek, František (ACS applied materials & interfaces, 2018)
A colloidal system able to act as a miniature reactor for on-demand release of reactive payloads has been demonstrated. The system is based on submicrometer aggregates consisting of anionic liposomes that act as storage reservoirs for the reactants, superparamagnetic iron oxide nanoparticles (SPIONs) that enable magnetic positioning in space and controlled release of reactants from the liposomes by radiofrequency stimulation, and an oppositely charged polyelectrolyte (poly-l-lysine) that keeps the constituent elements within the aggregates at a defined ratio. The kinetics of liposome-PLL-SPION heteroaggregation was systematically mapped and a suitable composition of the liposome bilayer was found such that the system exhibits stability at ambient conditions and radiofrequency triggered release at physiological temperature. The functionality of the system was demonstrated using a reaction between resazurin and ascorbic acid. The ability to release the reactants on-demand at defined time points was demonstrated. The system opens up opportunities for the controlled local delivery of unstable of highly bioactive molecules produced in situ and on demand from stable precursors.
Keywords: Nanoparticles; Liposomes; magnetismus; Temperature; Magnetics; teplota; nanočástice; liposomy